Standards System for Supporting High-Quality Development - Gan Yong; Yin Weilun; Wang Haizhou; Chen Xuedong; Fan Weicheng; Lin Zhongqin; Ouyang Zhiyun (中国工程科学, 2021)
The standards system for supporting high-quality development is based on the development concept of “innovation, coordination, green, openness, and sharing” and supports the all-round, high-quality development of China’s economy, society, and ecology. Conducting strategic research on this standards system plays a basic and leading role in promoting economic development, ecological environment quality, and social governance level, and is significant for meeting people’s needs for a better life. In this article, we analyze the concept of high-quality development as well as the connotation and characteristics of the standards system for supporting high-quality development, and study the difference between the high-quality development standards system and existing systems. Moreover, this study presents the main directions and implementation paths for the standards system by 2025 and 2035, focusing on agriculture, manufacturing, services, social governance, ecological civilization, and other key areas. Furthermore, we propose corresponding countermeasures in aspects of top level design, standardization policies, standardization capability improvement, and standardization personnel training, hoping to provide references for the development of the aforementioned key areas and for the decision making of relevant government departments.